Determinan Tingkat Kesejahteraan Keluarga di Masa Pandemi Covid-19 dalam Perspektif Ekonomi Islam - Dania Hellin Amrina; Asih Agustriyani; Asriani (Universitas Pembangunan Nasional Veteran Jakarta, 2023)
This study aims to analyze how much influence income level, lifestyle, and number of family members have on the level of family welfare in the view of Islamic Economics in Kampung Jati Anom Kel. Srengsem Kec. Panjang. This study uses a quantitative approach which is descriptive statistics. The sampling technique uses Quota Sampling. The population is 294 families and the sample is 100 families. Collecting data using questionnaires/questions and documentation techniques. Partially, the results of this study indicate that the variable income level and lifestyle affect the level of family welfare, while the variable number of family members has no effect. Simultaneously, the level of income, lifestyle, and number of family members affect the level of family welfare. From an Islamic perspective, real welfare is feeling sufficient, this is still not felt by most of the people of Kampung Jati Anom Kel. Srengsem Kec. Panjang.